Dinamika Politik Persetujuan Bersama tentang Penetapan Desa Adat di Kabupaten Rokan Hulu Tahun 2014 - Haryo Suganda; Raja Amin (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This study is motivated the identification of policies issued by the regional Government of Rokan Hulu in the form of Regulatory region number 1 by 2015 on the determination of the village and Indigenous Village. Political dynamics based on various interests against the manufacture of, and decision-making in the process of formation of the corresponding local regulations determination of Indigenous Villages in the Rokan Hulu is impacted to a very significant amount of changes from the initial draft of the number i.e. 21 (twenty one) the village became Customary 89 (eighty-nine) the Indigenous Villages who have passed. Type of this research is a qualitative descriptive data analysis techniques. The research aims to describe the State of the real situation in a systematic and accurate fact analysis unit or related research, as well as observations of the field based on the data (information). Method of data collection was done with interviews, documentation, and observations through fieldwork (field research). The results of the research on the process of discussion of the draft local regulations and mutual agreement about Designation of Indigenous Villages in the Rokan Hulu is, showed that the political dynamics that occur due to the presence of various political interests, rejection orally by Villagers who were judged to have met the requirements of Draft Regulations to be formulated and the area for the set to be Indigenous Villages, and also there is a desire from some villages in the yet to Draft local regulations in order to set the Indigenous village, there is a wide range of interests of these aspects influenced the agreement to assign the entire local village which is in the Rokan Hulu become Indigenous village, and the village of Transmigrationinto administrative Villages where the initiator of the changes in the number of IndigenousVillages in the Rokan Hulu it is the desire of the local Government of its own.